Open and endovascular surgery for stenosis of the peripheral regions of arteriovenous fistula - Z. B. Kardanakhishvili (Bûlleten' Sibirskoj Mediciny, 2019)
Vascular access is the cornerstone of hemodialysis. With vascular access dysfunction, the results of treatment of patients with stage 5 chronic kidney disease significantly deteriorate. One of the most common causes of vascular access failure is peripheral venous stenosis. Despite the variety of initiating factors, the morphological substrate of stenotic damage to the arteriovenous fistula (or arteriovenous anastomosis) in most cases is neointimal hyperplasia. Stenotic lesions of the arterivenous fistula are strongly associated with an increased risk of thrombosis and loss of vascular access. There are 4 typical localizations of stenosis: arteriovenous or arteriograft anastomosis, stenosis of the juxta-anastomotic segment of the fistula, stenosis of the functional segment of the fistula, and stenosis of the cephalic arc.The most common indication for surgical treatment is vascular access failure; less common indications are clinical symptoms of venous insufficiency.There are various methods of open reconstruction of the stenotic segment of the fistula vein: resection, prosthetics with a synthetic vascular graft, prosthetics or plastic repair of the autologous vein wall, complete or partial drainage of the prestenotic segment of the vein, etc. Currently an alternative method of stenosis repair using endovascular interventions is gaining popularity. In contrast to central vein stenosis, where endovascular interventions are the gold standard, in peripheral vein stenosis it is only an adjuvant method. Complications of endovascular interventions are extremely rare.Despite the fact that endovascular interventions have almost absolute probability of technical success, the primary patency is not high and is about 50% in six months. The use of bare stents is not accompanied by an increase in primary patency. The use of stent-grafts can increase the primary patency, especially in the plastic repair of challenging stenoses of the graft-vein anastomosis or cephalic arch.Many issues related to endovascular interventions remain unresolved, which requires further research.